Development of a frugal solar still using phase change material and nanoparticles integrated with commercialization through a novel economic model - Sonker V.K.; Chakraborty J.P.; Sarkar A. (My University, 2025)
A frugal solar still has been proposed with cylinders filled with paraffin wax and blended with nanoparticles; significant enhancement in distillation output has been observed. The yield of solar distillate increased by 43.50% when PCM has been used, as compared to the base case when no PCM has been used. The yield increased by 32.90% when PCM and nanoparticles have been used, as compared to the case when only PCM has been used. The evaporative heat transfer coefficient has been increased in the case of NPCM. The proof of concept on a novel frugal solar still has been established and it has been observed that the cost of distilled water reduced from Rs. 5/L to Rs. 3/L (40% reduction in cost). It has also been observed that the payback period for our proposed novel economic model (SSNPCM) is 4.3 years which justifies the deployment of our solar still in resource constrained setting. This will also facilitate commercialization of the product. © 2022 Elsevier Ltd